2020
DOI: 10.1007/s10546-020-00515-y
|View full text |Cite|
|
Sign up to set email alerts
|

Transition Periods in the Diurnally-Varying Atmospheric Boundary Layer Over Land

Abstract: The atmospheric boundary layer undergoes transitions between stable and convective states. Over land, in undisturbed conditions, these transitions occur daily in the morning and late afternoon or early evening. Though less well studied and presenting more challenges than the fully stable and 2 fully convective states, such transitions have been the subject of growing interest over the last few decades. During transitions, all forcings are weak, and few simplifications are possible. Factors such as terrain, rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 109 publications
(132 reference statements)
0
23
0
1
Order By: Relevance
“…Angevine et al (2001) have shown that the most extreme day-to-day variations in the duration of the morning transition were found on days with cloud influence at Cabauw tower in the Netherlands. The daytime convective BL over Amazonia is generally cloud influenced and rarely cloud-free (Betts et al, 2009); therefore days with cloud influence during the morning transition stage are not excluded from the analysis.…”
Section: The Morning Transition Boundary Layer and Its Relation To The Afternoon Shdeep Convectionmentioning
confidence: 99%
“…Angevine et al (2001) have shown that the most extreme day-to-day variations in the duration of the morning transition were found on days with cloud influence at Cabauw tower in the Netherlands. The daytime convective BL over Amazonia is generally cloud influenced and rarely cloud-free (Betts et al, 2009); therefore days with cloud influence during the morning transition stage are not excluded from the analysis.…”
Section: The Morning Transition Boundary Layer and Its Relation To The Afternoon Shdeep Convectionmentioning
confidence: 99%
“…The increase in the number concentration between morning and noon is coincident with the time when surface sensible heat flux becomes positive, the nocturnal BL is eroded and the convective BL is rapidly built (Stull, 1988;Angevine et al, 2020; https://doi.org/10.5194/acp-2021-314 Preprint. Discussion started: 20 April 2021 c Author(s) 2021.…”
Section: Diurnalmentioning
confidence: 99%
“…The morning transition (MT) is of interest for weather and air quality forecast as it impacts the distribution of temperature, humidity, and pollutants in the developing CBL (e.g., Holtslag et al., 2013; Morbidelli et al., 2011). Nevertheless, it is difficult to investigate and understand since important drivers including advection, shear, and entrainment are typically simplified or neglected (Angevine et al., 2020; Bange et al., 2007; Wildmann et al., 2015).…”
Section: Introductionmentioning
confidence: 99%